Firm-level evidence on productivity differentials, turnover, and exports in Taiwanese manufacturing - Bee-yan Aw; Xiaomin Chen; Mark J. Roberts (Fondazione Eni Enrico Mattei (FEEM), 1997)
Recent dynamic models of firm entry and exit emphasise the relationship between a firm's productivity and the decision to enter or exit. If firm turnover is driven by productivity differentials then the reallocation of resources across firms at the micro level can have important implications for aggregate or industry-level productivity change. Using comprehensive firm-level panel data from the Taiwanese Census of Manufactures for the years 1981, 1986, and 1991, this paper documents the extent of firm turnover in both the domestic and export markets, uses index numbers to measure differences in total factor productivity between entering, exiting, and continuing firms, and quantifies the contribution of firm turnover to industry productivity improvements. We find significant differences in productivity across manufacturing firms and these differences are reflected in turnover patterns. Cohorts of new firms have lower average productivity than incumbents but are themselves a heterogeneous group. The more productive members of the group survive and, in many cases, their productivity converges to the productivity level of incumbents. Exiting firms are also less productive than survivors. Differences in productivity are also reflected in movements of firms in and out of the export market. Firms that remain exporters over multiple years have the highest productivity while beginning exporters, whether they are new firms or older firms, follow behind them. All are more productive on average than firms that exit the export market who, in turn, are more productive than firms that never exported. These patterns are consistent with the view that both the domestic and export market sort out high productivity from low productivity firms and that the export market is a tougher screen. Unlike the findings for most other countries, the differential productivity between entering and exiting firms is an important source of industry-level productivity improvements in the Taiwan manufacturing sector.
Keywords: O12; D24; O47; F14; 330; Total factor productivity; Firm turnover; Exports; Taiwan manufacturing sector; Produktivität; Absatz; Export; Verarbeitendes Gewerbe; Taiwan